Advantages of stereolithographic 3D printing in the fabrication of the Affiblot device for dot-blot assays - Novotny, Jakub; Svobodova, Zuzana; Ilicova, Marie; Košťálová, Jana; Hrušková, Dominika; Bílková, Zuzana; Foret, Frantisek (Springer, 2024)
In stereolithographic (SLA) 3D printing, objects are constructed by exposing layers of photocurable resin to UV light. It is a highly user-friendly fabrication method that opens a possibility for technology sharing through CAD file online libraries. Here, we present a prototyping procedure of a microfluidics-enhanced dot-blot device (Affiblot) designed for simple and inexpensive screening of affinity molecule characteristics (antibodies, oligonucleotides, cell receptors, etc.). The incorporation of microfluidic features makes sample processing user-friendly, less time-consuming, and less laborious, all performed completely on-device, distinguishing it from other dot-blot devices. Initially, the Affiblot device was fabricated using CNC machining, which required significant investment in manual post-processing and resulted in low reproducibility. Utilization of SLA 3D printing reduced the amount of manual post-processing, which significantly streamlined the prototyping process. Moreover, it enabled the fabrication of previously impossible features, including internal fluidic channels. While 3D printing of sub-millimeter microchannels usually requires custom-built printers, we were able to fabricate microfluidic features on a readily available commercial printer. Open microchannels in the size range 200-300 mu m could be fabricated with reliable repeatability and sealed with a replaceable foil. Economic aspects of device fabrication are also discussed.
Výhody stereolitografického 3D tisku při výrobě zařízení Affiblot pro dot-blot testy
Keywords: 3D printing; Microfluidics; Prototyping; Dot-blot; Antibody; 3D tisk; Mikrofluidika; Prototypování; Dot-blot; Protilátka